The Contribution of the Water LIFE Kids Cup Fishing Tournament to the Charlotte County, Florida Economy - Chuck Adams; Betty Staugler; Alan Hodges (EDIS)
FE700, an 8-page paper by Chuck Adams, Betty Staugler, and Alan Hodges, describes an assessment of the economic activities in Charlotte County associated with the Water LIFE Kids Cup Fishing Tournament, to help tournament planners better anticipate the economic benefits associated with such community activities. Published by the UF Department of Food and Resource Economics, October 2007.